White Matter Integrity Underlies the Physical-Cognitive Correlations in Subjective Cognitive Decline - Wei, Yi-Chia; Hsu, Chih-Chin Heather; Huang, Wen-Yi; Chen, Yao-Liang; Lin, Chemin; Chen, Chih-Ken; Lin, Chen; Shyu, Yu-Chiau; Lin, Ching-Po (Frontiers in Aging Neuroscience, 2021)
Objective: Although previous studies postulated that physical and cognitive decline co-developed in preclinical dementia, the interconnected relationship among subjective cognitive complaints (SCCs), objective cognitive performance, and physical activity remained hazy. We investigated the mediating roles of physical activity between subjective and objective cognition. Diffusion tensor imaging (DTI) was utilized to test our hypothesis that brain white matter microstructural changes underlie the physical-cognitive decline in subjective cognitive decline (SCD). Methods: We enrolled cognitively normal older adults aged > 50 years to the Community Medicine Research Center of Keelung Chang Gung Memorial Hospital during 2017-2020. Regression models analyzed mediation effects of physical activity between subjective and objective cognition. The self-reported AD8 questionnaire assessed SCCs. The SCD group, defined by AD8 score ≥ 2, further underwent diffusion MRI scans. Those who agreed to record actigraphy also wear the SOMNOwatchTM for 72 hours. Spearman’s correlation coefficients evaluated the diffusion indices’ associations with physical activity and cognitive performance. Results: In 95 cognitively normal older adults, the AD8 score and Montreal Cognitive Assessment (MoCA) score were mediated partially by the metabolic equivalent of the International Physical Activity Questionnaire Short Form (IPAQ-SF MET) and fully by the sarcopenia score SARC-F. That is, the relation between SCCs and poorer cognitive performance was mediated by physical inactivity. The DTI analysis of 31 SCD participants found that the MoCA score correlated with mean diffusivity at bilateral inferior cerebellar peduncles (ICP) and right cortical spinal tract (p < 0.05, false discovery rate [FDR]-corrected). The IPAQ-SF MET was associated with fractional anisotropy (FA) at the right posterior corona radiata (PCR) (p < 0.05, FDR-corrected). In fifteen SCD participants who completed actigraphy recording, the patterns of physical activity in terms of intradaily variability and interdaily stability highly correlated with FA of bilateral PCR and left superior corona radiata (p < 0.05, FDR-corrected). Conclusions: This study addressed the role of physical activity in preclinical dementia. Physical inactivity mediated the relation between higher SCCs and poorer cognitive performance. The degeneration of specific white matter tracts underlay the co-development process of physical-cognitive decline in SCD.